La evolución de la industria del sector automotriz en Japón, crecimiento de las empresas automotrices japonesas y su impacto en la economía de Japón (The evolution of the automobile industry in Japan, growth of the Japanese automobile enterprises and their impact in the Japanese economy) - Blanco Jiménez, Mónica; Guerra Moya, Sergio Armando; Villalpando Cadena, Paula; Castillo, Jorge (Facultad de Contaduría Pública y Administración U.A.N.L., 2010)
Abstract. The main question of this research was to know if the growing of the Japanese automotive Industry Sector has an impact on the Japanese economy or is the export dynamics evolution of automotive company that has enabled significant growth. We analyze the evolution of the Japanese automotive industry starting with a review of the global automotive industry and ending with the analysis of case study as the Japanese company, Toyota. It’s important to know that since 1952, the Japanese government started a policy to encourage the automotive industry through the provision of cheap credit, tax and labor market protection, and emerging companies like Toyota, Nissan, Mazda and Honda. These facts eventually became highly competitive the Japanese companies that created and flexible production systems, which are more efficient and reduce production costs, help increase sales and foreign trade.